2007
DOI: 10.7205/milmed.172.11.1190
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Heart Rate Variability in War Veterans with Post-Traumatic Stress Disorder after Myocardial Infarction

Abstract: Post-MI patients with PTSD have higher sympathetic and lower parasympathetic heart rate modulation activity, compared with patients with MI and no PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…These results extend knowledge and support of HRV decline (Lakusic et al, 2007) found in cardiac patients with posttraumatic stress disorder (PTSD) compared to similar patients without PTSD. A majority (80%) of subjects in the current research with MST had PTSD, which supports previous findings of increased adjusted odds ratio (AOR) of developing current (AOR =7.15, 95% CI = 4.03-12.69) and lifetime (AOR = 7.03, 95% CI = 5.05-9.79) PTSD following MST .…”
Section: Chapter 5 Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These results extend knowledge and support of HRV decline (Lakusic et al, 2007) found in cardiac patients with posttraumatic stress disorder (PTSD) compared to similar patients without PTSD. A majority (80%) of subjects in the current research with MST had PTSD, which supports previous findings of increased adjusted odds ratio (AOR) of developing current (AOR =7.15, 95% CI = 4.03-12.69) and lifetime (AOR = 7.03, 95% CI = 5.05-9.79) PTSD following MST .…”
Section: Chapter 5 Discussionsupporting
confidence: 72%
“…PTSD participants (n = 14) had significantly higher resting heart rate and lower HRV measures of LF, HF, and LF/HF ratio (p < .001 all) than controls (n = 25) (Cohen, Benjamin, et al, 2000). Post-MI veterans with PTSD (n = 34) had significant differences in HRV indices with decreased R-R intervals (p = .02) and HF (p = .03) and increased LF (p = .01) and LF/HF ratio (p = .02) compared to post-MI veterans without PTSD (n = 34) (Lakusic et al, 2007). Mortality risk was increased threefold (hazard ratio 3.45; 95% CI = 1.57-7.60; p = .002) in patients with an ICD who had PTSD (n = 38) over those with and ICD and no PTSD (n = 109) (Ladwig et al, 2008).…”
Section: Anxietymentioning
confidence: 94%
See 1 more Smart Citation
“…High HRV has been considered adaptive given that much support has been found for its relationship with greater capacities to regulate stress, emotional arousal, resistance to stress, and positive emotions (Bomstein & Suess, 2000;Forges, Doussard-Roosevelt, Portales, & Greenspan, 1996). Low HRV, contrarily, has been considered maladaptive given consistent findings of its relationship with pathophysiology (Bemtson et al, 1996;Dekker et al, 2000) and with several psychological disorders (Carney et al, 2000;Lakusic, 2007;McCraty, Atkinson, Tomasino, & Stuppy, 2001;Rechlin, Weis, Spitzer, & Kaschka, 1994). Given the use of HRV as an outcome measure of autonomic resiliency, the current study was undertaken in order to examine whether HRV can also predict psychological variables of resilience-general stress resiliency, attachment security, and resilient personality factors.…”
Section: Purpose Of the Current Studymentioning
confidence: 97%
“…These same researchers have also disregarded the meaningfulness of the LF/HF ratio, (Carney et al, 2000;Rechlin, Weis, Spitzer, & Kaschka, 1994). There have also been several studies showing that low HRV is related to mental health disorders related to disruptions of autonomic function, such as Post-traumatic Stress Disorder (PTSD; Cohen et al, 2000;Lakusic, 2007;Lee & Theus, 2012). One major cluster of symptoms associated with PTSD is hyperarousal (e.g., irritability, hypervigilance, difficulty concentrating, being easily startled, difficulty falling or staying asleep), which suggests dysregulation within the autonomic nervous system, specifically attenuated parasympathetic activity and elevated sympathetic activity (Blechert, Michael, Grossman, Lajtman, & Wilhem, 2007).…”
Section: Frequency Analysesmentioning
confidence: 99%